Simpson, M.G. & Rebman, J.P. (2021) Research in Boraginaceae: A new variety of Cryptantha maritima, Cryptantha pondii resurrected, and Johnstonella echinosepala transferred back to Cryptantha. Phytotaxa 509: 185–210. - Simpson, M.g.; Rebman, Jon P. (Phytotaxa, 2021)
Erratum